2009
DOI: 10.1021/ed086p1219
|View full text |Cite
|
Sign up to set email alerts
|

Adapting to Student Learning Styles: Engaging Students with Cell Phone Technology in Organic Chemistry Instruction

Abstract: In the ClassroomThe infamous, dreaded "orgo", a marathon of memorization. Unfortunately, that's how all too many college students view their first exposure to organic chemistry. (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…The meaningful understanding of science requires students to be able to apply scientific concepts and principles to solve problems in a variety of situations and unfamiliar contexts (Cheng et al 2014). However, traditional views of science education that employ behaviouristic approaches in teaching and that mainly focus on fact memorization and rote learning do not really fit the needs of today's learners (Pursell 2009). The emergence of serious games undoubtedly brings a huge opportunity for science education and holds the potential not only to help learners construct accurate intuitive understandings of science but also to prepare them for future learning through a more flexible and powerful method of instruction (Clark et al 2009).…”
Section: Serious Games In Science Educationmentioning
confidence: 99%
“…The meaningful understanding of science requires students to be able to apply scientific concepts and principles to solve problems in a variety of situations and unfamiliar contexts (Cheng et al 2014). However, traditional views of science education that employ behaviouristic approaches in teaching and that mainly focus on fact memorization and rote learning do not really fit the needs of today's learners (Pursell 2009). The emergence of serious games undoubtedly brings a huge opportunity for science education and holds the potential not only to help learners construct accurate intuitive understandings of science but also to prepare them for future learning through a more flexible and powerful method of instruction (Clark et al 2009).…”
Section: Serious Games In Science Educationmentioning
confidence: 99%
“…has been demonstrated that educational technologies within classroom settings can increase student engagement and one's motivation to study (Pursell, 2009), it is not surprising that students were receptive to incorporating mobile technologies in the laboratory setting. While QR codes were found to be a useful learning aid, the use of QR codes alone had no significant relationship with performance on practical examinations.…”
Section: Anatomical Sciences Education Month 2014mentioning
confidence: 99%
“…Despite the heated discussion and commercial promotion of using cell phones for distance English learning, the empirical exploration on C-learning in formal English education settings was hard to locate and few have had paid attention to the activity design. Researchers suggested that the success of C-learning depended on an appropriate activity design to persuade students to use cell phones for educa tional purposes (Librero et al, 2007;Prensky, 2005;Pursell, 2009). Therefore, a C-learning activity was carefully designed for this study.…”
Section: C-learning In Efl Teaching In Chinamentioning
confidence: 99%